2019
DOI: 10.12998/wjcc.v7.i4.500
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic plasma exchange and continuous renal replacement therapy for severe hyperthyroidism and multi-organ failure: A case report

Abstract: BACKGROUND Severe hyperthyroidism is a life-threatening exacerbation of thyrotoxicosis, characterized by high fever and multiorgan failure. The most common medical treatments are administration of antithyroid drugs and radioactive iodine, and thyroidectomy. In some patients, antithyroid therapy is limited due to serious adverse effects or failure to control disease progression. In some extreme cases, such as thyroid storm, conventional therapy alone does not yield effective and rapid improvement b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…26 When used with TPE, case reports have showed clinical improvement and a reduction of FT4 by 44% to 80% and TRAb by 70% after 3 to 4 days of CRRT and TPE. [27][28][29] The only case report of CRRT used in isolation demonstrated a reduction of FT4 by 80% and near normalization of FT4 after 1 week of CRRT. 26 The mechanism by which CRRT reduces thyroid hormone and leads to clinical improvement is unclear.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…26 When used with TPE, case reports have showed clinical improvement and a reduction of FT4 by 44% to 80% and TRAb by 70% after 3 to 4 days of CRRT and TPE. [27][28][29] The only case report of CRRT used in isolation demonstrated a reduction of FT4 by 80% and near normalization of FT4 after 1 week of CRRT. 26 The mechanism by which CRRT reduces thyroid hormone and leads to clinical improvement is unclear.…”
Section: Discussionmentioning
confidence: 98%
“…26 Most patients in these case reports had multiorgan failure and the main indications for initiating CRRT was fluid removal or oliguric renal failure. 26,27 CRRT may be combined concurrently with TPE [27][28][29] or in isolation. 26 When used with TPE, case reports have showed clinical improvement and a reduction of FT4 by 44% to 80% and TRAb by 70% after 3 to 4 days of CRRT and TPE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the hyperthyroid state, the insulin level decreases because of the increase in the glomerular filtration rate, 43,52 and the ratio of C-peptide to proinsulin is very low. 38,53 These factors aggravate the underlying abnormal glucose metabolism and intensify insulin deficiency, which in this case served as a trigger for the onset of DKA. It has been reported that the identification of TS tends to be delayed in patients with DKA because of suppression by fever 13,44,45 and relatively low thyroid hormone levels.…”
Section: Case Presentationmentioning
confidence: 88%
“…11 The literature related to TS was searched from 2016 to 2019, and the clinical characteristics of gastrointestinal symptoms in patients with TS were found to mainly be nausea, and the main cause of TS to be Graves' disease with unknown or poor compliance with anti-thyroid drugs (Table 3). [33][34][35][36][37][38][39][40][41][42][43][44][45][46] Considering that hiccups are not common in either DKA or TS, we speculate that the incidence of intractable hiccups is rare when DKA overlaps with TS. By carefully searching the literature, we found the following related cases.…”
Section: Case Presentationmentioning
confidence: 99%